The interface of gambling and cultural practices: a Tongan male perspective in Aotearoa | New Zealand - Fehoko, Edmond S.; Bellringer, Maria E.; Fairbairn-Dunlop, Peggy (Frontiers in Sociology, 2023)
Introduction For over 30 years, Pacific people have been identified as more at risk of developing problem gambling behaviors than the general population. That observation has not changed despite the increase in treatment service providers, Pacific gambling literature and problem-gambling literature, which are primarily quantitative-based. This article explores the interface of gambling and cultural practices from a Tongan male perspective to consider whether status advancement and rank contribute to the problem-gambling statistics and the qualitative reasons why Tongan peoples engage in gambling activities. Methods A phenomenological approach using the talanoa research method was employed to carry out this study. A total of 46 Tongan males participated in this study. Interpretative Phenomenological Analysis was employed to interpret the data. The ethical approval reference number 16/452 for this research was granted by the Auckland University of Technology Ethics Committee (AUTEC). Results Participants noted the concept of fatongia as a motivating factor for Tongans to engage in gambling activities, which, in turn, elevates family and village status and rank. Discussion Strategies and recommendations around raising cultural awareness with treatment providers are critical to understanding Tongan gambling in New Zealand.